Pengaruh Pemberian Daun Sungkai (Peronema Canescens) Terhadap Jumlah Eosinofil Pada Kulit Mencit (Mus Muscullus) Alergi - Pratama, Riski Aditya (STIKes Medistra Indonesia, 2023)
Allergy is an exaggerated reaction originating from the immune system to a substance that works using immunoglobulin E (IgE) activity due to the presence of certain allergens. One of the activated cells is eosinophil during inflammation. Sungkai leaves (Peronema canescens) contain flavonoids, saponins, alkaloids and phenols which have anti-inflammatory activity, which helps in the healing process. This study was conducted to determine the effect of sungkai leaf smearing on increasing or decreasing the number of eosinophil cells in the skin of allergic mice induced by ovalbumin. This study used a pure experiment with post-test only method with a control group design, using 27 male mice divided into 3 groups, namely control, allergic, and allergic groups which were given Sungkai leaf smear. In this study, the parameters observed were a decrease or increase in the number of eosinophil cells in the skin of allergic mice treated with Sungkai leaf smear. The results of this study showed that out of the 3 treatment groups, there was an increase in the number of eosinophil cells in the skin of mice in the allergic mice group and the allergic mice group that was smeared in the statistical test using the One Way Anova test and there was an effect in the form of an increase in the number of eosinophils with a p value of 0.000. So it can be concluded that there is an effect of giving Sungkai leaves (Peronema canescens) on the number of eosinophil cells in the skin of allergic mice.